问题 解答题
计算下面各题,怎样简便就怎样算.
7
13
×
3
4
+
3
4
×
6
13
3
7
÷
7
11
+
4
7
÷
7
11
12
7
÷(
2
3
-
1
4
5
9
+
5
9
÷
5
3
16
5
×
1
2
÷
2
5
6×(
7
9
+
5
6
)÷
29
5
答案

(1)

7
13
×
3
4
+
3
4
×
6
13

=

3
4
×(
7
13
+
6
13

=

3
4
×1

=

3
4

(2)

3
7
÷
7
11
+
4
7
÷
7
11

=(

3
7
+
4
7
)×
11
7

=1×

11
7

=1

4
7

(3)

12
7
÷(
2
3
-
1
4

=

12
7
÷
5
12

=4

4
35

(4)

5
9
+
5
9
÷
5
3

=

5
9
+
1
3

=

8
9

(5)

16
5
×
1
2
÷
2
5

=

8
5
÷
2
5

=4;

(6)6×(

7
9
+
5
6
)÷
29
5

=(6×

7
9
+6×
5
6
)÷
29
5

=(

14
3
+5)÷
29
5

=

29
3
÷
29
5

=1

2
3

多项选择题
单项选择题 B1型题